2016
DOI: 10.1186/s12915-016-0323-9
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin 2 signaling plays a critical role in neural crest cell migration

Abstract: BackgroundCollective neural crest cell migration is critical to the form and function of the vertebrate face and neck, distributing bone, cartilage, and nerve cells into peripheral targets that are intimately linked with head vasculature. The vasculature and neural crest structures are ultimately linked, but when and how these patterns develop in the early embryo are not well understood.ResultsUsing in vivo imaging and sophisticated cell behavior analyses, we show that quail cranial neural crest and endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…During embryonic development, Ang2 is expressed in the developing placenta, with its expression being highest during early gestation [26], and participates in spiral artery remodeling [6]. It was also demonstrated that Ang2 is important for cranial neural crest cell migration, thus for vertebrate head patterning [27].…”
Section: Role Of Ang2 In Physiological Functionsmentioning
confidence: 99%
“…During embryonic development, Ang2 is expressed in the developing placenta, with its expression being highest during early gestation [26], and participates in spiral artery remodeling [6]. It was also demonstrated that Ang2 is important for cranial neural crest cell migration, thus for vertebrate head patterning [27].…”
Section: Role Of Ang2 In Physiological Functionsmentioning
confidence: 99%
“…HCR is a relatively new tool for mutant embryo analysis, just beginning to be used to analyze mutant embryos [59][60][61][62] . We used HCR to examine the expression of multiple genes in a single tissue by combining it with Imaris image analysis software.…”
Section: Discussionmentioning
confidence: 99%
“…Live embryos for time lapse imaging were mounted on EC culture dorsal-side down beginning at HH9 or 10 modifying the protocol of (Chapman et al, 2001;McKinney et al, 2016) such that the EC culture was plated with only 500uL of liquid to reduce light scattering. Confocal z-stacks using 488nm laser to image Dendra2 of the transgenic quail and 633 for DiD were collected every 7 minutes for up to 12 hours with a 10x 0.45 objective.…”
Section: Microscopymentioning
confidence: 99%
“…A better understanding of the dynamics and interplay between the neural crest and tissues through which cells travel would shed light on the mechanistic basis of collective cell migration for which neural crest cells are an exemplary model (Noden, 1988;Kontges and Lumsden, 1996;Noden and Trainor, 2005;McLennan et al, 2015;McKinney et al, 2016). Detailed experiments would confirm the robustness of the stereotypic neural crest stream shape and length over the course of early head development under the constraints of a growing microenvironment.…”
Section: Introductionmentioning
confidence: 99%